Sobre repertório, professores e cinema : o manejo do repertório de filmes de professores de história na composição de suas aulas - Peruffo, Gabriela do Amaral (2021)
This thesis analyses how history teachers handle their inventory when choosing movies for their classes. Teachers were observed in order to discover their criteria of selection when using movies for their classes, what place these movies have in their class plans. The choice of movies was made by their potential of presenting to the subject of History other versions and interpretations about facts. We analyze the connections between Cinema and Education to enhance the questions about curriculum of History within the national referential for the Basic Education with the theoretical support of Foucault by focusing on the idea of problematizing but considering that there is no absolute truth. The concept of repertoire was developed from Thierry de Duve and his idea of collection, understanding the notion of canon as a privileged part within the repertoire. With this, it was possible to address the concept of repertoire of approach of Bourdieu with the notions of distinction, cultural capital, cultural arbitrary, in order to think of it as an individual and collective construction within the school. The handling of a repertoire is considered the exercise of composition of classes to meet specific demand of subjects, this notion is supported in the idea of curation as considered by Miriam Celeste Martins and Gisa Picosque, and in the form of organization according to the Atlas Mnmosyne elaborated by Aby Warburg to plan classes. The empirical method involved interviews with five teachers – the subjects of the research are in different moments of their teaching trajectories and they teach in different schools of the public and private network of Porto Alegre. A script of interviews was written with open questions to allow the teachers to narrate their experiences and speak about strategies, criteria, and ways of creating in class. The empirical material was analyzed to dialogue with the repertoire and its handling, and three referential markers were created in three moments and they appear in the elaboration of the classes. There are three stages that, articulated, explain different ways in which the teachers handle their repertoire. The strategies of handling the choice of movies from their repertoire with the notion of curation; the different ways of thinking the exhibition of the movies inside the class and the post-movie moment, the strategy created by the teachers to validate the exhibition of the movies to their students. By looking at the markers separately, it was possible to understand how they always showing the handle of repertoire as an ability developed by teachers from their accumulation of experience and constant decision-taking to compose their classes. By analyzing with the teachers how they handle their repertoire of movies, it was perceived the diversity of ways of creating from the multiple possibilities of composition of classes.